The correlation between the presence of exostoses and temporomandibular joint dysfunction - doi:10.5020/18061230.2008.p174 - Ana Karolina Nunes Furtado; Ana Karina de Moraes Leite; Raquel Araújo de Albuquerque; Ana Paula Veras Sobral (Universidade de Fortaleza, 2012)
Objective: To evaluate the association between exostosis and / or torus along with the variables: sex, age, ethnic aspects, anatomic site and temporomandibular joint dysfunction (TMD). Methods: This was a retrospective and serial case study. The sample consisted of 75 patients, of both genders, aged between the 1st and 10th life decades, sorted from the Center of Oral facial Pain of Pernambuco Dentistry School at the State University of Pernambuco (CDO-FOP-UPE). The data were obtained by means of patients' interview, complemented by analyses of clinical records, besides intraoral examination for the identification, description and classification of the exostosis and/or palatal and/or mandibular torus. The descriptive statistical analyses was accomplished considering anthropometric and demographic data of the patients, applying Pearson's chi-square test and Fisher's exact test (p>5). Results: The torus was present in 20.0% of the cases, of which 60.0% were palatal torus. The majority of the cases occurred in male patients (25.0%), brown in color (24.3%) and at the 5th decade of life (23.1%), with no association between its presence and the sex, age or race. It was observed that the displacement of the disc with reduction was the type of intra-capsular TMD most related to these alterations. Conclusion: In the studied sample, the presence of torus was registered in 20.0% of the studied subjects, although there was no statistically significant association between the presence of exostosis and the analyzed variables - sex, race and age. The displacement of the disc with reduction was the temporomandibular joint dysfunction most associated to the presence of torus.